2021
DOI: 10.1002/anie.202015910
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Phosphorylation and Concomitant Oligomerization of Deoxynucleosides to form DNA

Abstract: Recent demonstrations of RNA–DNA chimeras (RDNA) enabling RNA and DNA replication, coupled with prebiotic co‐synthesis of deoxyribo‐ and ribo‐nucleotides, have resurrected the hypothesis of co‐emergence of RNA and DNA. As further support, we show that diamidophosphate (DAP) with 2‐aminoimidazole (amido)phosphorylates and oligomerizes deoxynucleosides to form DNA—under conditions similar to those of ribonucleosides. The pyrimidine deoxynucleoside 5′‐O‐amidophosphates are formed in good (≈60 %) yields. Intriguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 69 publications
2
37
0
Order By: Relevance
“…[2][3][4][5][6] Mainly, chemical activation strategies are deployed in polymerisation reactions, 3,7 and template-directed primer extension of sequences rely on ex-situ activation of monomers. 8,9 We base this study on 2´,3´-cyclic mononucleotides (cNMP) which (a) possess an intrinsically activated phosphate; (b) are products of several prebiotic phosphorylation and nucleotide syntheses; [10][11][12][13][14] and (c) are products of neutral to alkaline chemical and enzymatic hydrolyses of RNA. [15][16][17][18][19] In comparison, the dry polymerisation of 3´,5´-cyclic GMP, [20][21][22] did not foster the copolymerisation of the other nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Mainly, chemical activation strategies are deployed in polymerisation reactions, 3,7 and template-directed primer extension of sequences rely on ex-situ activation of monomers. 8,9 We base this study on 2´,3´-cyclic mononucleotides (cNMP) which (a) possess an intrinsically activated phosphate; (b) are products of several prebiotic phosphorylation and nucleotide syntheses; [10][11][12][13][14] and (c) are products of neutral to alkaline chemical and enzymatic hydrolyses of RNA. [15][16][17][18][19] In comparison, the dry polymerisation of 3´,5´-cyclic GMP, [20][21][22] did not foster the copolymerisation of the other nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to prebiotic phosphorylation have exploited activated sources of phosphate. Phosphoramidates, including diamidophosphate (DAP), have been highlighted as powerful prebiotic phosphorylation reagents 17 23 . However, a prebiotically relevant method to directly recycle orthophosphate back into DAP has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that increased temperature (55 °C) and wet‐dry cycling led to simultaneous formation of (a) oligodeoxynucleotides with predominantly 3′,5′‐phosphodiester linkages and (b) 5′‐polyphosphorylated species – once again pointing to the versatility of DAP to act both as a phosphorylating and activating agent. Interestingly, pyrophosphate‐linked oligonucleotides, which are usually formed in other oligomerization using phosphorimidazolides, were minor components of the reaction products as reported in this work [29] . The mild conditions under which DAP can phosphorylate ribonucleosides to form 2’,3’‐cyclophosphates that are activated towards ring‐opening reaction makes them suitable for ligation reactions.…”
Section: Dap: Reactions With Organic Substratesmentioning
confidence: 52%
“…reported that the DAP‐mediated phosphorylation chemistry under the paste conditions could be extended to deoxynucleosides as well but required change of the activator from imidazole to 2‐aminoimidazole. [29] The phosphorylation proceeded primarily at the 5′‐position affording the 5’‐amidophosphate nucleotides (Scheme 6 ). Once again, the pyrimidine deoxynucleosides reacted more efficiently than their purine counterparts.…”
Section: Dap: Reactions With Organic Substratesmentioning
confidence: 99%
See 1 more Smart Citation